Dynamic activity of military transportation investigation at the construction site - Mykhailovska, Olena; Nesterenko, Tetiana (Academic journal Industrial Machine Building Civil Engineering, 2019)
In the paper it is confirmed that any theoretical data inferior to precisely measured data due to the impossibility of considering all the factors influencing on the oscillation process. The fluctuations magnitude of a non-residential building in Poltava and the dynamic influence on the building structure and the people who can be there periodically are experimentally investigated. To evaluate the vibration impact, it is necessary to compare measured data with the permissible level of vibration in public buildings. The recommendations for the further building exploitation are based on the building structures vibration acceleration measurements results.